EFEKTIFITAS PENAMBAHAN MEDIA ORGANIK EKSTRAK UBI JALAR (Ipomoea batatas L) PADA PERTUMBUHAN SUBKULTUR ANGGREK Cattleya sp. - Shinta Nurdika Meilani; Septarini Dian Anitasari; Fatimatuz Zuhro (Florea : Jurnal Biologi dan Pembelajarannya, 2017)
Orchids (Chattleya sp) is popular plant which is favorted by peoples and has higt economic value. It’s price Rp. 562,000 / plant. Tissue culture technique is needed to produce this flower quicky than conventional technique. This study have aims to determine the effect of some medium concentration of organic sweet potato (Ipomoea batatas L) on growing Cattleya sp and for knowing the best of concentration on the growth of  Chattleya sp. The method used was Completely Random Design (RAL) with four of factors, that is: 0 g / L, 75 g / L, 150 g / L, and 300 g / L. The results were analyzed with Anova test and Duncan test multiple ranger test at the level of 5%. Each treatment was repeated six times. Parameters were observed are the number of new shoots, long leaf, number of leaves, leaf width, long roots, and height of the plant for 5 weeks. Based on the results of analysis showed that the sweet potato extract on 150 g / L concentration give the best results in long root parameter, the concentration of 75 g / L gived the best results to long leaf parameter and concentration of 300 g / L gived the best effect against leaf width. Same concentrations of sweet potato did not give significantly effect to number of new shoots, plantlets height, and number of leaves.